Time Value of Money : Concepts and Applications - Ahamed, Naseem (Indian Journal of Finance, 2020)
The case, at its core, explored the concepts of time value of money from the perspective of a newly joined intern in Money Smart Consultancy Pvt. Ltd. The value of money doesn’t stay static because of certain factors such as inflation at play. The value of money changes as it moves on the timeline either forward or backward. The concept of compounding was used for finding out the equivalent amount of money in the future when one moves forward on the timeline. Different types of cash flows such as lump sum, annuity, perpetuity, etc. were discussed to make the reader understand through the questions of the protagonist of this case. The rates used for compounding/discounting are indicative of the cumulative risk assumed by the investor for which he/she ought to be compensated. Through different cases of various companies, Joy discussed the concepts and their applications with his intern.